2018
DOI: 10.1371/journal.pone.0204961
|View full text |Cite
|
Sign up to set email alerts
|

Femoral antecurvation—A 3D CT Analysis of 1232 adult femurs

Abstract: IntroductionFor optimal treatment of femoral fractures, it is essential to understand the anatomical antecurvation of the human femur. Recent clinical studies have highlighted the problem of distal anterior encroachment or even perforation of the nail tip. The aim of this study was to accurately describe the femoral antecurvation in a large cohort. Another objective was to identify the most important influences on femoral antecurvation, such as age, femur length, gender and ethnicity.MethodsA three dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 26 publications
4
29
1
Order By: Relevance
“…1 and 2). As shown in prior studies, this method provides accurate and consistent results 13,14 . The operators who defined the bony landmarks were an experienced trauma, hip and pelvic surgeon (MH) and a trauma surgery resident (DT) with focus on pelvic trauma along with a Stryker employee (BH).…”
supporting
confidence: 64%
“…1 and 2). As shown in prior studies, this method provides accurate and consistent results 13,14 . The operators who defined the bony landmarks were an experienced trauma, hip and pelvic surgeon (MH) and a trauma surgery resident (DT) with focus on pelvic trauma along with a Stryker employee (BH).…”
supporting
confidence: 64%
“…In order to ensure better proximal pressure distribution, the larger femoral prosthesis stem would be chosen, and the femoral stem length would be increased, thereby increasing the point between the cortex and the impact of risk within the plants. [26][27][28] In addition, the existing biological femoral stem prosthesis is mainly designed based on patients in European or American, and therefore the LK. LCU femoral stem prosthesis of the same length used in this study was bound to increase the risk of collision when implanted into the body of Asians.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a comparison of different ethnic groups in America, Asian populations showed an increased risk of AFF relative to other races 9 12 . Asian women have a more curved femur than Caucasians, while Africans tend to have the straightest femurs 13 – 15 , which would explain the high prevalence of AFF in Asians. It has also been reported that diaphyseal AFF is more common than subtrochanter AFF in Korean patients with AFF 6 , 16 .…”
Section: Introductionmentioning
confidence: 99%